2016
DOI: 10.1007/s00068-016-0735-9
|View full text |Cite
|
Sign up to set email alerts
|

Management, treatment and outcomes of acute appendicitis in an elderly population: a single-center experience

Abstract: Severe forms of acute appendicitis and post-operative morbidity are higher in the elderly population. Cardiac disease is the only predictor for increased morbidity. Although CT scan was performed universally in the elderly group, it did not appear to increase time from presentation to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…19 General Surgery, Salerno University, Salerno, Italy. 20 Department of Surgery, Macerata Hospital, Macerata, Italy. 21 General, Mininvasive and Bariatric Surgery Unit, Department of Advanced Medical and Surgical Sciences, University of Campania Luigi Vanvitelli, Caserta, Italy.…”
Section: Availability Of Data and Materials Not Applicablementioning
confidence: 99%
See 2 more Smart Citations
“…19 General Surgery, Salerno University, Salerno, Italy. 20 Department of Surgery, Macerata Hospital, Macerata, Italy. 21 General, Mininvasive and Bariatric Surgery Unit, Department of Advanced Medical and Surgical Sciences, University of Campania Luigi Vanvitelli, Caserta, Italy.…”
Section: Availability Of Data and Materials Not Applicablementioning
confidence: 99%
“…Furthermore, according to almost all authors, elderly patients were significantly more likely than other age groups to have complicated appendicitis with perforation or abscess. The complicated appendicitis rate ranges from 18 to 70% [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (compared to a rate ranging from 3 to 29% among patients younger than 65 years old). The reason for this high risk of perforation could be the vascular sclerosis that the vermiform appendix develops in elderly patients and the narrowing of the lumen by fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In der aktuellen Literatur zur akuten Appendizitis wird der Anteil der Altersappendizitis zwischen 5-10 % angegeben. Charakteristisch für die Altersappendizitis sind schwere und unspezifische klinische Verläufe, die mit einer hohen Komplikationsrate verbunden sind [29]. In Anbetracht der komplikationsarmen bzw.…”
Section: Indikationsstellung Zur Baunclassified
“…Although appendicitis is often thought of as a disease of the young, it has been reported that there has been a higher proportion of the population aged 60 or over with AA in recent years in association with increasing life expectancy [1,[8][9][10][11]. However, it has also been speculated that whether this change was a real event occurring on a national level for the United States [1].…”
Section: Introductionmentioning
confidence: 99%